Angle of the retinal of bacteriorhodopsin in blue membrane - Tóth-Boconádi, R. (1989)
The electric dichroism of purple and cation-depleted (blue) membrane was measured in a.c. electric fields at saturation. A decrease of 5.5° in the direction of the chromophore transition moment with respect to the membrane normal was found upon removal of cations from purple membrane.